Positive LGI1 Antibodies in CSF and Relapse Relate to Worse Outcome in Anti-LGI1 Encephalitis - Cui, Li-li; Boltze, Johannes; Zhang, Yan (Frontiers in Immunology, 2021)
Objective This single-center study was conducted in a cohort of patients with anti-LGI1 encephalitis to investigate the factors related to their functional recovery. Methods We retrospectively collected the clinical information of patients admitted to Xuanwu Hospital from January 2014 until December 2019, and followed up for at least 12 months. Results A total of 67 patients were included, and 57 completed the 12-month follow-up. Most of the patients (55/57, 96.5%) achieved functional improvement after immunotherapy, and 26 (45.6%) became symptom-free. Compared to patients with complete recovery, patients with partial or no recovery had significantly higher incidences of consciousness disorders (25.8% vs. 0%, P<0.05) and positive LGI1 antibodies in cerebrospinal fluid (CSF) (71.0% vs. 46.2%, P<0.05). These patients also had a lower Barthel Index both upon admission and at discharge, as well as a higher incidence of relapse (25.8% vs. 3.8%; P<0.05 each). Univariate logistic regression showed that positive LGI1 antibodies in CSF and relapse were associated with incomplete recovery at 1-year follow-up (both P<0.05), but only relapse remained statistically significant after multivariate logistic regression (P=0.034). Conclusion Patients with LGI1 antibodies in CSF and those who relapsed were more likely to experience worse outcome. Early recognition of these patients, combined with more aggressive immunotherapy may result in better recovery.